Impact investing - Barber, Brad M.; Morse, Adair; Yasuda, Ayako (Journal of Financial Economics, 2021)
We show that investors derive nonpecuniary utility from investing in dual-objective Venture Capital (VC) funds, thus sacrificing returns. Impact funds earn 4.7 percentage points (ppts) lower internal rates of return (IRRs) ex-post than traditional VC funds. In random utility/willingness-to-pay (WTP) models investors accept 2.5–3.7 ppts lower IRRs ex ante for impact funds. The positive WTP result is robust to fund access rationing and investor heterogeneity in fund expected returns. Development organizations, foundations, financial institutions, public pensions, Europeans, and United Nations Principles of Responsible Investment signatories have high WTP. Investors with mission objectives and/or facing political pressure exhibit high WTP; those subject to legal restrictions (e.g., Employee Retirement Income Security Act) exhibit low WTP.